Pengaruh Pendidikan Kesehatan Terhadap Pemberdayaam Masyarakat Dalam Upaya Pengendalian Penyakit - Raspiyahni R; Maharani Br Barus; Adelina Fitry R Lubis; Farah Sabila; Baldatun Thoibah; Maulidya Permata; Nisrina N (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Community empowerment is a process of providing information continuously and continuously by increasing awareness and ability to improve health status. Despite various disease control efforts carried out by the government and health institutions, there are still challenges in changing people's behavior. This research uses a quantitative approach, the research population is people involved in related health education programs. The sample will be selected from various community groups who have participated in health education programs, including individuals of various ages, educational backgrounds, and socioeconomic status. Data collection was carried out through surveys and structural interviews that had been determined related to community empowerment through education. From the results of the research we conducted, it is known that many people who actively participate in educational activities are between the ages of 18-25 years, this is in line with the attendance percentage of 70.58% of respondent participation. This is also supported by technological sophistication, where health education is not only supported by direct activities, but can be carried out virtually. There are several recommendations in efforts to increase community empowerment, including: Community-based participation, increasing Health Literacy, Strengthening Local Resources, Collaboration with Related Parties, Providing Accessibility of Health Services, Use of Information Technology and Evaluation and Continuous Learning activities.